2022
DOI: 10.1177/21676968221098293
|View full text |Cite
|
Sign up to set email alerts
|

Age Matters? The Moderating Effect of Age on the Longitudinal Relationship between Upward and Downward Comparisons on Instagram and Identity Processes During Emerging Adulthood

Abstract: This study tested whether age moderates the longitudinal relationships between upward and downward comparisons on Instagram and three identity processes (i.e., commitment, in-depth exploration, and reconsideration of commitment). Two hundred and eleven British emerging adults completed two self-report surveys, two months apart, in early 2020. A cross-lagged panel model with interaction terms found that age moderated the relationships between both upward and downward comparisons on Instagram and commitment. Con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 77 publications
0
3
0
5
Order By: Relevance
“…Emerging adults explore their identities when seeking opportunities, sampling different careers, exploring romantic interests, and finding new hobbies (Arnett, 2015). Emerging adults' identity is key psychosocial functioning (Noon et al, 2022), and becomes more established as they gain an understanding of who they are, and their strengths and limitations (Arnett & Mitra, 2018). Schwartz and colleagues (2005) found that identity exploration may be especially likely for emerging adults who adopt individualization tactics such as taking financial responsibility and making independent decisions.…”
mentioning
confidence: 99%
“…Emerging adults explore their identities when seeking opportunities, sampling different careers, exploring romantic interests, and finding new hobbies (Arnett, 2015). Emerging adults' identity is key psychosocial functioning (Noon et al, 2022), and becomes more established as they gain an understanding of who they are, and their strengths and limitations (Arnett & Mitra, 2018). Schwartz and colleagues (2005) found that identity exploration may be especially likely for emerging adults who adopt individualization tactics such as taking financial responsibility and making independent decisions.…”
mentioning
confidence: 99%
“…Исследование было направлено на то, чтобы психологически операционализировать конструкт виртуальной идентичности, эмпирически исследуя ее процессы в российском контексте, предложив оригинальную шкалу оценки статусов виртуальной идентичности. В целом материалы, полученные в работе, согласуются с эриксоновскими (Эриксон, 2006) и неоэриксоновскими идеями касательно развития идентичности в период перехода к взрослости (Arnett, 2016;Crocetti, 2017;Noon et al, 2023;Schwartz et al, 2013), а также с положениями культурно-исторической теории Л.С. Выготского об инструментальности психики и знаково-символическом опосредствовании процессов личностного развития взрослеющей личности (Марцинковская, 2018; Рубцова, 2019; Сапогова, 2013; Солдатова, Войскунский, 2021).…”
Section: Discussionunclassified
“…Однако новая динамика перехода ко взрослой жизни, сопряженная с отсрочкой молодыми людьми этого перехода (длительное образование, откладывание брака и родительства, отказ от постоянной трудовой занятости и пр.) в индустриально развитых странах, получившая признание в отечественных (Клементьева, 2023; Манукян, 2022; Сапогова, 2013) и зарубежных (Arnett, 2016) исследованиях XXI в., отодвигает границу решения вопросов становления идентичности на более поздний срок -вплоть до 25-29 лет (Arnett, Mitra, 2020;Kroger et al, 2010;Noon et al, 2023;Vosylis et al, 2018). Таким образом, сегодня задача развития идентичности сохраняет свою актуальность у обучающейся молодежи в возрасте «формирующейся взрослости» (emerging adulthood) -18-25(29) лет.…”
Section: мв клементьева оценка статусов виртуальной идентичностиunclassified
“…Studies about social comparison are relevant to application because they focus on a psychological process that helps explain why people might incorporate (or resist) experiences within social media environments. Findings regarding identity processes and social comparisons have generally been mixed based on the platform studied, as well as the characteristics of the participants (e.g., age, gender, country where they reside; Noon, 2020; Noon et al., 2021; Noon et al., 2023). For example, a set of studies of American emerging adults found that those with less adaptive identity processes (e.g., rumination, diffuse‐avoidant style, lower identity clarity) tended to experience comparison of ability on social media, while those with more adaptive processes (e.g., informational and normative styles) tended to experience comparison of opinion (Yang et al., 2018a, 2018b).…”
Section: The Digital Contextmentioning
confidence: 99%